2018
DOI: 10.1002/chem.201802996
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a Needle in a Haystack: Isolation and Structural Characterization of Er2C94 as the Carbide Er2C2@D3(85)‐C92

Abstract: A method has been developed for isolating a pure sample of Er C from the myriad of fullerenes and endohedral fullerenes that are formed in the electric arc process. Crystallographic analysis of Er C in a cocrystal formed with Ni(OEP) reveals that the molecule is the carbide Er C @D (85)-C . Crystals of Er C @D (85)-C ⋅Ni(octaethylporphyrin)⋅2 C H are isostructural with those of Sm @D (85)-C ⋅Ni(octaethylporphyrin)⋅2 (chlorobenzene). Comparisons are made between the four crystallographically characterized endoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A more recent study reported the isolation and crystallographic elucidation of an Er-based CCMF, i.e. Er 2 C 2 @ D 3 (85)-C 92 , confirming again that larger cages tend to accommodate the carbide cluster 60. Moreover, for the even larger La 3+ ions, although the structures of some di-EMFs, namely La 2 @ D 2 (10611)-C 72 ,61 La 2 @ C s (17490)-C 76 ,62 La 2 @ D 3h (5)-C 78 ,63 La 2 @ I h (7)-C 80 ,64 and La 2 @ D 5 (450)-C 100 65 have been confirmed by single crystal XRD crystallography, the La 3+ ions are also more inclined to form carbide structures with some giant cages such as C 90–104 , which are rationalized by considering the synergistic effect of inserting a C 2 -unit on the stabilization of CCMFs both electronically and geometrically 4749…”
Section: Resultsmentioning
confidence: 66%
“…A more recent study reported the isolation and crystallographic elucidation of an Er-based CCMF, i.e. Er 2 C 2 @ D 3 (85)-C 92 , confirming again that larger cages tend to accommodate the carbide cluster 60. Moreover, for the even larger La 3+ ions, although the structures of some di-EMFs, namely La 2 @ D 2 (10611)-C 72 ,61 La 2 @ C s (17490)-C 76 ,62 La 2 @ D 3h (5)-C 78 ,63 La 2 @ I h (7)-C 80 ,64 and La 2 @ D 5 (450)-C 100 65 have been confirmed by single crystal XRD crystallography, the La 3+ ions are also more inclined to form carbide structures with some giant cages such as C 90–104 , which are rationalized by considering the synergistic effect of inserting a C 2 -unit on the stabilization of CCMFs both electronically and geometrically 4749…”
Section: Resultsmentioning
confidence: 66%